Determinants of Construction Workers’ Safety Performance: Examining the Effects of K3 Implementation, Safety Training, Safety Leadership, and Work Discipline - Herotje Siwi; Jedithjah Naapia Tamedi Papia; Franciscus Josep Tulung; Meike Negawati Kesek (Malaqbi Publisher, 2026)
The construction project is a risky undertaking that involves exposure to several types of occupational hazards. Consequently, it is necessary to improve the safety performance of construction workers to ensure successful completion of the project and reduce risk at the workplace. This study will analyze the factors affecting safety performance by looking at the impact of K3, safety training, safety leadership, and work discipline on safety performance. A quantitative explanatory research approach was applied in this study, whereby a sample of 150 construction workers was identified via survey technique. Data collection was carried out using structured questionnaires rated on a five-point Likert scale and analyzed using multiple linear regression with SPSS software. The results reveal that K3 implementation, safety training, safety leadership, and work discipline have a positive and significant impact on safety performance. Out of all four variables, work discipline affects safety performance the most, followed by safety leadership, K3 implementation, and safety training. In this respect, the model has an explanatory power of 67.9%.